2008
DOI: 10.1161/atvbaha.107.161737
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Activated Protein C Attenuates Endothelial Injury and Inhibits Procoagulant Microparticles Release in Baboon Heatstroke

Abstract: Objectives-We tested the hypothesis that the antithrombotic and cytoprotective effects of recombinant human activated protein C (rhAPC) protect baboons against the lethal effects of heatstroke. Methods and Results-Fourteen anesthetized baboons assigned randomly to rhAPC (nϭ7) or control group (nϭ7) were heat-stressed in a prewarmed incubator at 44 to 47°C until systolic blood pressure fell below 90 mm Hg, which signaled severe heatstroke. rhAPC was administered intravenously (24 g/kg/h) for 12 hours at onset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
42
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 31 publications
3
42
0
Order By: Relevance
“…No pharmacological treatment has been found to be beneficial. Antipyretics have no role in heat stroke and may be toxic to the liver, whereas experimental findings in a primate classic heat stroke model do not support the clinical use of corticosteroids or activated protein C in the prevention or treatment of classic heat stroke (48,49).…”
Section: Treatmentmentioning
confidence: 95%
“…No pharmacological treatment has been found to be beneficial. Antipyretics have no role in heat stroke and may be toxic to the liver, whereas experimental findings in a primate classic heat stroke model do not support the clinical use of corticosteroids or activated protein C in the prevention or treatment of classic heat stroke (48,49).…”
Section: Treatmentmentioning
confidence: 95%
“…Recombinant human activated protein C (rhAPC) has been approved in the United States for the treatment of severe sepsis and has anti-inflammatory and anticoagulant properties that warrant consideration for the treatment of heat stroke. In heat stroke patients and experimental models, rhAPC attenuated inflammation, resolved multi-organ system dysfunction, and improved survival (5,10,23). However, the efficacy of rhAPC was dependent on the timing of administration and specific characteristics of the patient population and did not protect against mortality in all heat stroke models, indicating that additional studies are needed to warrant its use as a heat stroke treatment (10,23,87).…”
Section: Prevention and Treatmentmentioning
confidence: 99%
“…Early work by Satta and co-workers for example has demonstrated that LPS treatment increases TM activity on monocyte-derived MPs by up to 80% (135). Coelevated TM and MP levels in serum have also been observed during systemic inflammatory response syndrome (SIRS) in humans and during heat stroke in baboons (18,116), while recent work by Duchemin et al (40) points to an influence of circulating MPs on the "TM resistance" of patients suffering from myeloproliferative neoplasm.…”
Section: Posttranslational Regulationmentioning
confidence: 99%